2017
DOI: 10.1001/jamainternmed.2017.2668
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking and Silent Electronic Health Record Use in Ambulatory Visits

Abstract: to construct 3 categories of mammogram history: (1) never had a mammogram, (2) had over a year ago, and (3) had less than a year ago. We tested for differences in importance evaluations by mammogram history using ordered logit regression. Analyses applied the GfK survey weights to adjust for nonresponse bias and panel nonresponse to produce nationally-representative estimates. The study was determined to be exempt from review by the University of Minnesota institutional review board.Results | Fifty-eight (14.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 6 publications
0
18
1
Order By: Relevance
“…Thus, working with scribes can be a solution to reduce physician multitasking, which potentially can reduce medical errors. 32 Our physicians did not report increased stress when working with scribes, which contrasts with prior literature. A recent qualitative study found that physicians reported increased stress due to workflow changes when working with scribes who were MAs or nurses with expanded roles.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, working with scribes can be a solution to reduce physician multitasking, which potentially can reduce medical errors. 32 Our physicians did not report increased stress when working with scribes, which contrasts with prior literature. A recent qualitative study found that physicians reported increased stress due to workflow changes when working with scribes who were MAs or nurses with expanded roles.…”
Section: Discussioncontrasting
confidence: 99%
“…Although physician gaze at the computer has predicted less patient satisfaction 3 and, in this investigation, more silence, silence can also function as a facilitator of patient participation. 20,36 Thus, when patients use silence as an opportunity to speak, physicians may need to stop computer activity, look at the patient, and focus on what he or she is saying. 37 Finally, future research should explore what types of EHR screen content could be used to facilitate communication.…”
Section: Discussionmentioning
confidence: 99%
“…For example, charts, graphs, and images in the EHR lend themselves to screen sharing that could be used for patient education and shared decision-making. 20,37 Also, given that important issues clinicians and patients discuss in the consultation often are not documented in the EHR, 38 future research should examine what effects on data entry into the EHR are associated with whether clinicians enter data during the consultation or wait to do so when the patient has left.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians spend one-third of outpatient visits using electronic health record (EHR) systems, either in silence or by multitasking [ 1 - 3 ]. Multitasking occurs when someone performs 2 or more tasks simultaneously.…”
Section: Introductionmentioning
confidence: 99%